Digital Image Copyright Protection with Spatial Domain Public Image Watermarking Scheme - Mawaddah Harahap; Johannes Rianto Malau; Tentus Natoka Simangungsong; Davin Winata; David Hadyanto (Information Technology and Science (ITScience), 2022)
The resulting digital image certainly has the copyright attached to the image. There needs to be protection of digital image works because the form of storage of digital imagery works that are vulnerable to piracy, claims of unauthorized authorities, illegal duplication, or unauthorized modification. The Spatial Domain Public Image Watermarking method is used to protect digital imagery using applications designed to facilitate the watermarking process on several different digital images as well as with different image formats. The reason for using this method is because it has low complexity. In this study, it consisted of three processes carried out, namely the process of making watermarking, the process of checking watermarking and comparison of input imagery and image results. In the process of making watermarking do image input as a watermarking media, input inserted imagery in the form of binary images / text, key inputs and watermark results. In process of checking watermarking performs image input that becomes watermark media, watermark results input, key input, and checking results. The process of creating watermarking takes a relatively short time while the process of extracting watermarking processing time depends on the size of the image file. From some image testing conducted using imagery with three formats, namely: JPG with an average time accuracy of 9:5,310(42.15%), .GIFs with an average time of 8:27.207(21.63%), and. BMP has an average time accuracy of 5:2.989(36.22%). Thus, the determination of the image format used is adjusted to the original image, so that it can perform time efficiency.